PROSPECTS OF BIOLOGICALLY ACTIVE SUBSTANCES BASED ON AMINOHYDROXYBENZOIC ACIDS AND THIOUREA FRAGMENT - Haydarova Hulkar Akhtamjon kizi; Niyazov Laziz Nurkhanovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Thiourea derivatives have been widely studied and are used as the most important reagents for organic synthesis, as well as biologically active substances and drugs in medicine [1,2]. One of them is para-aminosalicylic acid, which is a pharmacological substance. Also, scientific research has been conducted on the fact that the compound formed with thiourea exhibits various properties. The article reviews the latest trends in the production and synthesis of biologically active substances . In addition, substances based on thiourea and para-aminosalicylic acid have been studied .